Can Wheat Germ Have a Beneficial Effect on Human Health? A Study Protocol for a Randomised Crossover Controlled Trial to Evaluate its Health Effects - Moreira-Rosário, A (2017)
INTRODUCTION: Cardiovascular diseases (CVD) are the leading cause of mortality worldwide and diet is an important contributor to CVD risk. Thus, several food derivatives are being investigated for their beneficial impact on reducing cardiometabolic risk factors, either in risk groups or in healthy population as a preventive measure. Wheat germ is a food by-product with high nutritional value, especially as a concentrated source of dietary fibre and essential fatty acids, but its incorporation into the diet has been rare up to now. Previous studies do not clarify the hypothesised potential causal relationship between the consumption of wheat germ and benefits for human health. METHODS AND ANALYSIS: We are conducting a randomised, double-blinded, crossover, placebo-controlled clinical trial designed to assess the physiological effects of daily consumption of wheat germ-enriched bread (containing 6 g of wheat germ) compared with non-enriched bread, over a 4-week period with a 15-week follow-up, in a healthy human population. A total of 55 participants (healthy volunteers, aged 18-60) have been recruited from the Porto metropolitan area in northern Portugal. Our aim is to evaluate the health effects of wheat germ on blood cholesterol and triglycerides, postprandial glycaemic response, gastrointestinal function and discomfort, and changes in intestinal microbiota and insulin resistance as secondary outcomes. The study follows the best practices for evaluating health claims in food according to the European Food Safety Authority (EFSA) scientific opinion, namely random allocation, double blinding, reporting methods to measure and maximise compliance, and validated outcomes with beneficial physiological effects as recommended by EFSA. ETHICS AND DISSEMINATION: The study has been approved by the Health Ethics Committee of São João Hospital Centre (156-15) and the Ethics Committee of Faculty of Medicine of the University of Porto (PCEDCSS-FMUP07/2015). Results will be disseminated through peer-reviewed publications and presentations at international scientific meetings.